“Alô (escola do) cupido, meu coração já não aguenta mais”: violências (d)e gênero nas relações de namoro de jovens escolares - Guimarães, Ananda Neves Arnoud (2019)
The youth is a period in which there is a high social expectation. This is when a greater search for autonomy is usually initiated, the building of stronger bonds of friendship and the experience of the first affective-sexual relations. These relationships, especially dating, are attributed the place of nonviolence, space for affection and tenderness. Studies on gender violence have emphasized relationships between adult couples, sometimes obscuring the serious occurrence of violence in youth affective-sexual relationships. However, this high incidence phenomenon has resulted in serious health consequences for young people, with short, medium and long term effects (depression, anxiety, suicidal thoughts). Therefore, this research aimed to analyze, from a gender perspective, the meanings and senses attributed to the experiences of violence in the dating relationships of high school students from a state public school, located in João Pessoa-Paraíba, and how these young people understand the role of the school in preventing and coping with this type of violence. The specific objectives were: to identify the meanings and senses attributed to the dating experiences by the young students; analyze how gender norms pervade relationships and occasional expressions of violence in student dating; analyze the possible differences and similarities of violence suffered and perpetrated by female and male youths in their dating relationships; identify if/how students understand the school and its social actors as a space to support and prevent gender violence in dating. For this, 18 students from the 2nd and 3rd years of high school of that school, aged 16 to 18 years old, who were dating or have ever experienced a dating relationship. Data collection was performed through semi-structured interviews and empirical data were analyzed based on Cultural Analysis. The research findings indicate the occurrence of various violence (physical, psychological and sexual) in young dating; however, this violence is invisibilized and signified as natural from relationships; Gender norms permeate the meanings and experiences of dating and violence, placing girls in a place of passivity and sentimentality, while boys would play a more active and less emotional role in relationships. Beyond gender issues, religion has presented itself as an important marker in the construction of meanings about these relationships. The youngsters identified the school as a potent space in the prevention and coping with dating violence, through focused and punctual activities promoted by school agents and peer training.